2017
DOI: 10.1101/182238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pangenomic analysis reveals pathogen-specific regions and novel effector candidates inFusarium oxysporumf. sp.cepae

Abstract: Abstract-148

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Analysis of 60 F. graminearum isolates form North America identified an accessory genome close to 1700 genes that seems to concentrate in AT‐rich regions, probably centromeres or telomeres (Kelly & Ward, ). Similar results have been obtained for F. fujikuroi (Chiara et al ., ; Niehaus et al ., ), and F. oxysporum (Armitage et al ., ). Together, these studies have focused either on geographically delimited isolates or have compared a handful of isolates.…”
Section: Metabolic Complexitymentioning
confidence: 97%
“…Analysis of 60 F. graminearum isolates form North America identified an accessory genome close to 1700 genes that seems to concentrate in AT‐rich regions, probably centromeres or telomeres (Kelly & Ward, ). Similar results have been obtained for F. fujikuroi (Chiara et al ., ; Niehaus et al ., ), and F. oxysporum (Armitage et al ., ). Together, these studies have focused either on geographically delimited isolates or have compared a handful of isolates.…”
Section: Metabolic Complexitymentioning
confidence: 97%
“…The emergence of new effector genes in individual pathogen lineages played an important role in the evolution of pathogenicity and changes in host range (Liao et al, 2016). This is supported by comparative genomics studies that showed that most effector genes are taxonomically restricted (or orphans) to a set of closely related species or even to a subset of individuals within a species (Stukenbrock et al, 2012;Grandaubert et al, 2015;Plissonneau et al, 2016;Armitage et al, 2017). The gain and loss of individual fungal effectors are associated with major gains in pathogenicity (Huang et al, 2014;Yoshida et al, 2016;.…”
Section: Introductionmentioning
confidence: 95%